Root canal morphology variation in mandibular posteriors: A cone beam computed tomography study - Christine Roy; Sandeep Pagare; Sonal Vahanwala; Mandavi Waghmare (Wolters Kluwer Medknow Publications, 2018)
Introduction: Cone beam computed tomography (CBCT) is a noninvasive method which has gained broad acceptance in dentistry in 10 years. CBCT has been designed as an improvement of the diagnostic tools available for dental applications. It aids in the diagnosis of variations of root canal morphology, endodontic and nonendodontic pathosis, assessing vertical root fractures, analysis of root resorption defects, and presurgical assessment of apicoectomy procedures. Methods: CBCT images of 400 mandibular second premolars, 400 first molars, and 400 second molars were collected from 200 patient's (bilaterally) using their CBCT images. The images were acquired retrospectively and studied for anatomy of root canals and their number. Results: In the present study type IV (89.7%) and type I (77.8%) canal configurations were the most commonly seen in the mesial and distal roots of first and second molars. They were seen in both males and females. Bilateral symmetry was noted in most of the mandibular second premolars for the males and females. They did not show any significant variations in their roots and root canal morphology; however, rare variations were noted in some cases. Conclusion: Present study indicated that we are able to provide more accurate diagnosis and treatment planning with this imaging modality, thereby limiting out any sort of missed canals and overlapping of anatomical structures.